Primitive neuroectodermal tumor coexistent with anaplastic ganglioglioma - Rezzan Erguvan-Onal; Cagatay Onal; Metin Sener; Bulent Mizrak; Erol Duran; Nasuhi Engin Aydin (Medicine Science, 2012)
Primitive neuroectodermal tumors are among the most common tumors of childhood and the most frequent location of them is cerebellum. Supratentorial primitive neuroectodermal tumors are uncommon. These tumors, regardless of site of origin, may show differentiations towards different cell lines such as glial, neuronal, and mesenchymal. To our knowledge, there is only one case in the literature describing ganglioglial differentiation in a cerebellar medulloblastoma. The presented report discloses a supratentorial primitive neuroectodermal tumor coexistent with anaplastic ganglioglioma in a 46-year-old man. Both components of the tumor disappeared after radiotherapy, with a proceedent glioblastomatous differentiation in the follow-up period. [Med-Science 2012; 1(1.000): 47-54]